Reconceptualizing cultural literacy as a dialogic practice. (1st November 2019) - Maine, Fiona; Cook, Victoria; Lähdesmäki, Tuuli
Abstract : Culture and heritage are plural and fluid, continually co-created through interaction between people. However, traditional monologic models of cultural literacy reflect a one-way transmission of static cultural knowledge. Using the context of a large European project and augmenting the work of Buber with models of literacy as social practice, in this article cultural literacy is reconceptualized as fundamentally dialogic. We argue that cultural literacy empowers intercultural dialogue, opening a dialogic space with inherent democratic potential. Considering implications for the classroom, we outline how a dialogic pedagogy can provide a suitable context for the development of young people's cultural literacy.